Social Protection and Labor : A Key Enabler for Climate Change Adaptation and Mitigation - Rigolini, Jamele (World Bank, Washington, DC, 2021)
This paper reviews the role of Social Protection and Labor in supporting both climate adaptation and mitigation efforts. The Climate Crisis is impacting the poor and vulnerable disproportionally, both as a consequence of climate shocks and through the distributional impacts of climate mitigation policies. The paper discusses how – even without explicit environmental objectives – Social Protection and Labor strengthens resilience against climate shocks. However, integrating crisis-sensitive elements into social protection and labor programs increases substantially their ability to respond to shocks. Social protection and labor programs also facilitate green and Just Transitions by supporting equitable policies and can ease transitions towards Green jobs. Finally, Social protection and labor programs can also directly support mitigation measures by positively affecting behaviors. While investments in climate-related Social Protection and Labor are rapidly expanding, its full potential to support adaptation, decarbonization and mitigation is still to be realized.